Prevalence of oral tori among medical and dental Students at the University of the West Indies - Arvind Babu Rajendra Santosh; Thaon Jones; Hima Venugopal; Keisha Smith; J Suzanne Turpin Mair; Mark Edwards; Errol Williams (University Library System, University of Pittsburgh, 2016)
Objective:  To determine the prevalence and gender variation of torus palatinus (TP) and torus mandibularis (TM) amongst medical and dental students at the Mona campus of the University of the West Indies. Subjects and Methods: The study observed 335 medical and dental students from the Mona campus of the University of the West Indies. Routine dental examinations were conducted to check the presence/absence of TP and TM by inspection and palpation. Results: The overall prevalence of TP and TM was 27.76%. The oral torus prevalence was as follows, torus palatinus was 44.08%, torus mandibularis was 36.55% and individuals with both torus palatinus and mandibularis was 19.35%. The study observed that the prevalence of TP and TM in females was 16.11% (54/335), and males 11.64% (39/335). It was also found that bilateral torus mandibularis (40.38%) was more prevalent than unilateral right torus mandibularis (36.53%) and unilateral left torus mandibularis (23.07%). Conclusions: The prevalence of TP and TM are comparatively higher than neighboring Caribbean nations and West African countries. Our observations also highlighted that TP is highly prevalent among various types of oral tori. The study also recorded higher prevalence of oral tori among females. Due to higher prevalence of oral tori among the study group, Jamaican dentists need be knowledgeable about the high prevalence and clinical significance of TP and TM for dental treatment.